Power system analysis - Saadat, Hadi (McGraw-Hill series in electrical and computer engineering.)
This is an introduction to power system analysis and design. The text contains fundamental concepts and modern topics with applications to real-world problems, and integrates MATLAB and SIMULINK throughout.